La estacionalidad en los precios agrarios durante la primera mitad del siglo XIX. Un caso especial: la cebada - Guigó Pérez, Miguel A. (Cuadernos de Estudios Empresariales, 2004)
The study of time series of prices is key in the understanding of their integration. Here we concern ourselves with Castilian cereal markets in the 19th century, particularly with the price of barley. Two different approaches are entertained: a separate study of each market, and a comparison of the results in the various markets. The understanding of seasonal behaviour is particularly important in this context. We study seasonal behaviour in two different ways: spectral analysis and univariate Box-Jenkins methods.
Keywords: Stacionality; spectral analysis; prices; univariate models